An automated non-intrusive fault injection technique integrated into the universal verification methodology - Lohmann, Douglas (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2019.